IFC Annual Report 2018 : Redefining Development Finance - International Finance Corporation (Washington, DC: International Finance Corporation, 2018)
IFC, a member of the World Bank Group, is the largest global development institution focused on the private sector in developing countries. Established in 1956, IFC is owned by 184 member countries, a group that collectively determines our policies. In FY18, IFC invested $23.3 billion, including nearly $11.7 billion mobilized from other investors. Our comprehensive approach helped businesses innovate, build internationally competitive industrial sectors, and create better jobs.